2002
DOI: 10.1111/1468-5906.00156
|View full text |Cite
|
Sign up to set email alerts
|

Religion and the Decision to Use Contraception in India

Abstract: This article investigates two hypotheses put forward to explain the effect of religion on the decision to use contraception in India. The first hypothesis is the "pure religion effect," that the intellectual content of religion influences contraceptive behavior. This hypothesis is explored by examining women's views on the theological content of Islam and Hinduism in relation to birth control, provided by a sample of 186 rural Hindu and Muslim women from southern India. The second hypothesis examined is the "c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 9 publications
2
50
1
Order By: Relevance
“…[14,15] The current use of contraceptive methods among young married women was almost similar for Hindus (41%) and Muslims (39%). [13,16] Contrary to our results, other studies have also revealed lower contraceptive use among Muslims. [17,18] Comparable findings for the current use have been reported in a study where acceptance of family planning was slightly higher in Muslims than in Hindus.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…[14,15] The current use of contraceptive methods among young married women was almost similar for Hindus (41%) and Muslims (39%). [13,16] Contrary to our results, other studies have also revealed lower contraceptive use among Muslims. [17,18] Comparable findings for the current use have been reported in a study where acceptance of family planning was slightly higher in Muslims than in Hindus.…”
Section: Discussioncontrasting
confidence: 99%
“…[16,20] The usage of pills, IUDs, and condoms was higher among Muslims (19%) as reported by Nazish, [16] National Family Health Survey. [21] This study also confirmed similar to other studies [13,16] that the traditional contraceptive methods were more popular among Muslim couples compared to Hindu couples. Our study also revealed that more than 14% of women had experienced their first sexual intercourse before marriage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other authors e.g. Amin et al [34], Iyer [35,36], Jeffrey and Jeffrey [37] have also reported on the different understandings within Islam on whether modern contraceptives are or are not permitted within the religion. In addition, people may join religions in order to access education, health care and material support and not because they agree to the doctrines or teachings of that particular faith [38].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of contraceptive use on fertility seem to be particularly important in developing countries. An example is Southern India, where 99% of Muslim and 81% of Hindu women suppose that their religion does not permit contraceptive use [17]. In line with this finding, Knodel et al [18] report-for Thailand-higher fertility as a result of less likely contraceptive use among Muslim women.…”
Section: Introductionmentioning
confidence: 97%